PO.6.128 Factors associated with survival and discontinuation of antimalarial agents in systemic lupus erythematosus: results from a swedish longitudinal registry - Walhelm, T; Wirestam, L; Parodis, I; Sjöwall, C (Lupus science & medicine, 2022)
PurposeHydroxychloroquine (HCQ) and chloroquine (CQ), referred to as antimalarial agents (AMA), are cornerstone drugs in systemic lupus erythematosus (SLE), which inhibit type I interferon release by interfering with toll-like receptors and increasing the pH in plasmacytoid dendritic cell lysosomes. AMA use has established benefits in SLE, such as improved prognosis and decelerated accrual of organ damage. Use of HCQ is safe for most patients and serious side-effects are uncommon, even during pregnancy. However, it is well-known that non-adherence to prescription of AMA is a considerable problem. The aim of this study was to evaluate factors associated with ongoing use and discontinuation of AMA in a Swedish SLE population.MethodsWe retrieved data from the Clinical Lupus Register in North-Eastern Gothia (Swedish acronym: KLURING), a longitudinal research and quality registry, including in effect all prevalent and incident cases of SLE in the Östergötland County from 2008 onwards. All included patients fulfilled the validated 1982 American College of Rheumatology (ACR) and/or the 2012 Systemic Lupus International Collaborating Clinics (SLICC) classification criteria and had been diagnosed from 1963 onwards. Data were retrieved from KLURING as well as from medical charts. Factors associated with ongoing use and discontinuation of AMA were investigated using logistic regression analysis, independent samples t-test and Pearson’s chi-square tests.ResultsA total of 218 subjects were included in the analysis (Table 1). The mean age at diagnosis was 43.4 years (3–85) and 89.9% were females. In total, 89.0% (194/218) had used AMA (ever) until analysis. Data from the last available visit indicated that 64.9% (126/194) were currently using AMA, mainly HCQ, yielding a daily mean HCQ equivalent dose of 218.2 mg. Among individuals who had discontinued AMA, 23.5% (16/68) had developed a contraindication, mostly retinopathy or other ophthalmologic conditions. Subjective side-effects were also common; the most frequently reported were gastrointestinal symptoms (n=16/35). Patients who discontinued AMA had a higher SLICC/ACR damage index (SDI) score at the last available visit (mean 2.90, standard deviation (SD) 2.73, mean follow-up 24.6 years) compared with patients on AMA (mean 1.83, SD 2.01, p=0.006, mean follow-up 22.4 years). No significant differences were found regarding gender or fulfilled ACR criteria. The most common patient-related factor associated with discontinuation was intentional non-adherence (low motivation; 14/15).Abstract PO.6.128 Table 1ConclusionsThe vast majority of patients in this cohort had been exposed to AMA, but approximately 1/3 discontinued AMA therapy during follow-up. The group of discontinued AMA users accrued more damage over time, and the length of follow-up in the two groups was not significantly different. No gender- or disease phenotype-related differences were observed. Factors contributing to discontinuation included contraindications, experienced side-effects, and intentional non-adherence.